2022
DOI: 10.1007/s00213-021-05982-w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress paradigm as a rat model of depression: facts, artifacts, and future perspectives

Abstract: Rationale The chronic mild stress (CMS) paradigm was first described almost 40 years ago and has become a widely used model in the search for antidepressant drugs for major depression disorder (MDD). It has resulted in the publication of almost 1700 studies in rats alone. Under the original CMS procedure, the expression of an anhedonic response, a key symptom of depression, was seen as an essential feature of both the model and a depressive state. The prolonged exposure of rodents to unpredictabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 283 publications
(497 reference statements)
3
66
0
Order By: Relevance
“…Previous studies with CMS variants stratifying mice for their susceptibility to stressinduced anhedonia showed that it can be associated with expression changes of several molecular and cellular markers of inflammation that are not displayed by resilience to anhedonic animals [22,95,[103][104][105]. For example, CMS-exposed susceptible-to anhedonia-mice revealed significant elevations of COX-1 and IDO expression in the midbrain raphe region, suggesting a possible interaction of neuroinflammation with altered 5-HT transmissionrelation mechanisms [95].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies with CMS variants stratifying mice for their susceptibility to stressinduced anhedonia showed that it can be associated with expression changes of several molecular and cellular markers of inflammation that are not displayed by resilience to anhedonic animals [22,95,[103][104][105]. For example, CMS-exposed susceptible-to anhedonia-mice revealed significant elevations of COX-1 and IDO expression in the midbrain raphe region, suggesting a possible interaction of neuroinflammation with altered 5-HT transmissionrelation mechanisms [95].…”
Section: Discussionmentioning
confidence: 96%
“…The remaining animals were considered as non-anhedonic (resilient to stress-induced anhedonia). Applied criterion of anhedonia was based on our previous results, which demonstrated that mice with a sucrose preference ≤65% showed a depressive-like syndrome, consisting in increased floating and decreased exploration, whereas stressed mice with a sucrose preference above this value did not display this behavioral phenotype [22,92,127].…”
Section: Chronic Stress Procedures and Determination Of Anhedoniamentioning
confidence: 99%
See 3 more Smart Citations